Pentingnya Feedback (Umpan Balik) Konstruktif Di Dalam Lingkungan Kerja - Josaphat Januar CPR; Sri Sundari; Marisi Pakpahan (EBISMAN eBisnis Manajemen, 2024)
In a global era that confronts organizations with intense business competition, performance assessments need to be carried out in a more aggregate or comprehensive manner that includes every member of the organization. The classical view that considers assessment only appropriate for subordinates must be abandoned and the assessment process must be carried out as something that has an impact on the organization. Therefore, a performance assessment strategy is needed that can reduce the obstacles that were previously needed. One strategy that can be used is to utilize constructive feedback so that problems that arise can be resolved and resolved in a focused manner. Constructive feedback is valuable response that focuses on improving employee performance. Constructive feedback is about being supportive so that the leader's feedback influences positive behavior change. In this article, the author conducted a literature study to find out the work culture at Netflix that makes employees feel at home, as well as analyzing the types and functions of feedback used by the company, so that they can achieve success. When it comes to constructive feedback, Netflix prioritizes an open and honest approach. Employees are expected to provide feedback to each other, including feedback to their superiors. It's important to remember that feedback can have a lasting positive impact on performance.